2018
DOI: 10.1111/jocn.14506
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in nursing and medical students’ attitudes, beliefs and behaviours about interprofessional work: An interprofessional placement in ambulatory care

Abstract: Interprofessional clinical placements are essential for students to understand interprofessional practice for better patient outcomes and developing their own perspective of future work within an interprofessional team. Ambulatory care is an ideal environment for nursing and other health professional students to engage in interprofessional clinical placements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 32 publications
1
28
0
1
Order By: Relevance
“…The literature search retrieved 3995 articles. After applying the inclusion and exclusion criteria and removing duplicates, 23 articles were included in the review [10,[29][30][31][32][33][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] (see PRISMA Flow diagram, Fig. 1).…”
Section: Trial Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search retrieved 3995 articles. After applying the inclusion and exclusion criteria and removing duplicates, 23 articles were included in the review [10,[29][30][31][32][33][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] (see PRISMA Flow diagram, Fig. 1).…”
Section: Trial Flowmentioning
confidence: 99%
“…The median number of MS in the IPE interventions was 100 . Nine studies (39%) reported data for first-year medical students [10,[29][30][31][36][37][38][39][40], five (22%) for second-year students [41][42][43][44][45], six (26%) for third-year students [32,[46][47][48][49][50], two (9%) for fourth-year [33,51] and one for sixth-year medical students [52]. No study reported interventions occurring in the fifth year.…”
Section: Participantsmentioning
confidence: 99%
“…After a community activity, the ISVS score increased 30 . A two-week-long clinical placement in ambulatory care improved the ISVS score 31 . This score also improved after an education program lasting 18 profession and interprofessional team.…”
Section: Discussionmentioning
confidence: 88%
“…48 The medical students' existing stereotypes about nursing students were challenged because they found that the nursing students had wider competencies than expected; this experience altered their attitude toward nursing students in general, as described in the literature. 24,25,39 Furthermore, by observing the nursing students' focus on the patients' activities in daily life, the medical students broadened their picture of the patient, from examining only X-rays and range of motion to having a more holistic view about what is important for patients in their daily life, e.g., how much weight the patient was allowed to carry when going shopping.…”
Section: Interprofessionalmentioning
confidence: 99%
“…21,22 Similar positive results have been reported from interprofessional clinical learning in outpatient clinics. [23][24][25] To our knowledge, a comparison of uniprofessional dyadic training versus interprofessional dyadic training of medical students in an authentic setup in a busy outpatient clinic has not been described. Based on the current literature, dyadic training seems to have the potential for peer learning in both situations.…”
Section: Introductionmentioning
confidence: 99%